PENGARUH PEMBERIAN BUAH NAGA MERAH TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI - Indra Yulianti; Veryudha Eka Prameswari; Indah Kusmindarti (MEDIA ILMU KESEHATAN, 2020)
Background: Red dragon fruit as a non-pharmacological alternative to lowering blood pressure in cases of hypertension Objective: prove the effect of giving red dragon fruit to reduce blood pressure in patients with hypertension.Methods: The research design used Quasy Experiment with pretest and posttest design with the control group. The population was 30 people with 15 people as the treatment group and 15 people as the control group. The sampling technique uses the Non Probability Sampling Technique with a purposive sampling method. Data were analyzed using paired t testResult: The results showed that the treatment group had an average systolic blood pressure of 153mmHg and a diastolic blood pressure of 86 mmHg. The results of testing the effectiveness of giving red dragon fruit to hypertensive patients with CI systolic> 1p value 0.096 <α, it can be concluded that H0 is rejected. As for the diastolic CI> 1p value 0.032 <α, it can be concluded that H0 is rejected, meaning that dragon fruit is effective in reducing systolic and diastolic blood pressure.Conclusion: Red dragon fruit can lower blood pressure. Because there is a content of iron and potassium which helps accelerate the circulation of oxygenated blood in the body Keywords: Blood pressure, hypertension, red dragon fruit